Benefits and Consequences of Police Crackdowns - Michael Scott (My University, 2016)
This response guide deals with police crackdowns, a response commonly used to address crime and disorder problems. Crackdowns involve high police visibility and numerous arrests. They may use undercover or plainclothes officers working with uniformed police, and may involve other official actions in addition to arrests. This guide provides the reader with on overview of the types of crackdowns, how crackdowns work to reduce crime, and how law enforcement can use crackdowns to address specific problems, such as robbery, burglary, gun-related crime, traffic problems, drug problems and street prostitution.